Comparison of neoadjuvant and adjuvant chemotherapy for operable triple-negative breast cancer before the era of immune checkpoint inhibitors: A retrospective study from the Japanese National Clinical Database-Breast Cancer Registry - Tomoe Taji; Hiraku Kumamaru; Yuki Kataoka; Kotaro Iijima; Hirofumi Suwa; Hiroshi Ishiguro; Naruto Taira; Takanori Ishida; Shigehira Saji (Breast)
Background: While neoadjuvant chemotherapy (NAC) is recommended for stage II-III triple-negative breast cancer (TNBC), its equivalence to adjuvant chemotherapy (AdjC) has been questioned based on a retrospective study using the National Cancer Database in the United States, which lacked adjustment for important covariates. Given the unlikelihood of new randomized trials being conducted, well-designed, large-scale, retrospective studies are needed. Patients and methods: We retrospectively analyzed operable TNBC patients from the Japanese National Clinical Database- Breast Cancer Registry (2012–2016). Inclusion criteria were clinical stage I-IIIB, estrogen receptor (ER) < 10 %, progesterone receptor (PgR) < 10 %, and HER2-negative. We excluded patients with carcinoma in situ, cT4a/T4c/T4d, cN3, cM1, bilateral breast cancer, male, non-epithelial tumor, no chemotherapy, no surgery and no follow-up. Primary and secondary outcomes of overall survival (OS) and recurrence-free survival (RFS) were compared between NAC and AdjC using Cox proportional Hazard regression among the exact matched cohort based on age, BMI, cT, cN, histology, ER/PgR positivity, chemotherapy regimen, breast operative technique, radiotherapy, and institution size. Results: Among 9,000 AdjC and 5,520 NAC patients, 3,256 matched cases were compared. OS and RFS were significantly worse for patients with NAC (Hazard Ratio 1.45 (95 % confidence interval 1.26–1.68) and 1.33 (1.19–1.49), respectively), particularly in patients <65 years, with stage II-IIIB, and with invasive ductal carcinoma. Conclusion: Patients with NAC had worse prognosis, possibly due to unadjusted confounders. Although the availability of immune checkpoint inhibitors (ICIs) limits the clinical impact, the result could provide supplemental insights for treatment decisions in patients who are not candidates for ICIs.